The Impact of Sleep Disturbance on Gut Microbiota, Atrial Substrate, and Atrial Fibrillation Inducibility in Mice: A Multi-Omics Analysis - Kun Zuo; Chen Fang; Yuan Fu; Zheng Liu; Ye Liu; Lifeng Liu; Yuxing Wang; Hongjiang Wang; Xiandong Yin; Xiaoqing Liu; Jing Li; Jiuchang Zhong; et al. (Metabolites, 2022)
This study examined the effect of sleep disturbance on gut microbiota (GM), atrial substrate, and atrial fibrillation (AF) inducibility. C57BL/6 mice were subjected to six weeks of sleep deprivation (SD) using the method of modified multiple-platform. Transesophageal burst pacing was performed to evaluate AF inducibility. Feces, plasma, and an atrium were collected and analyzed by 16s rRNA sequencing, liquid chromatography–mass spectrometry (LC-MS)-based metabolome, histological studies, and transcriptome. Higher AF inducibility (2/30 of control vs. 15/30 of SD, p = 0.001) and longer AF duration (p < 0.001), concomitant with aggravated fibrosis, collagen, and lipid accumulation, were seen in the SD mice compared to control mice. Meanwhile, elevated alpha diversity, higher abundance of Flavonifractor, Ruminococcus, and Alloprevotella, as well as imbalanced functional pathways, were observed in the gut of SD mice. Moreover, the global patterns for the plasma metabolome were altered, e.g., the decreased butanoate metabolism intermediates in SD mice. In addition, disrupted metabolic homeostasis in the SD atrium, such as fatty acid metabolism, was analyzed by the transcriptome. These results demonstrated that the crosstalk between GM and atrial metabolism might be a promising target for SD-mediated AF susceptibility.